Audiovisual narratives in Latin America in the face of insecurity: Bogotá, Guayaquil, and San Salvador on digital platforms - Arrobo-Agila, Juan Pablo; Suing, Abel; Barrazueta, Patricio (Street Art & Urban Creativity, 2025)
Latin American cities have experienced a transformation in their urban narratives through digital media. This research compares the narratives present in photo reports and podcasts in the cities of Bogotá, Guayaquil, and San Salvador, published on the most viewed social media platforms between January 2024 and June 2025. The study is based on the hypothesis that contemporary audiovisual formats reconfigure representations of urban creativity, generating new paradigms that reflect the cultural identities, social challenges, and creative potential of each metropolitan context. The purpose is to identify how production contributes strengths to address difficulties and propose solutions to the risks of public insecurity. A mixed methodology is used, applying interviews and content analysis. Photo reports are specialized, while podcasts offer an immersive experience. Understanding these differences helps content creators and researchers leverage the strengths of each medium to communicate effectively.